Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division Terhadap Pemahaman Konsep Siswa Kelas IX Pada Materi Listrik Statis - Fanani, Alifiah Rifky; Ratnawati, Uun; Inayah, Nailil (Indonesian Journal of Science Learning (IJSL), 2022)
This study aims to determine the effect of the STAD-type cooperative learning model on the conceptual understanding of class IX students of SMP Negeri 25 Surabaya on static electricity. The type of research used was pre-experimental with a pre-test and post-test control group design. The results of this study were (1) the normality test results for the students’ pre-test data were 0.075 > 0.05, which meant that the data were normally distributed, while the student post-test data were 0.052 > 0.05, which meant that the data were also normally distributed. (2) the results of the homogeneity test of students’ conceptual understanding with sig. based on mean 0.815 > 0.05 which means the data is homogeneous. (3) test the hypothesis using the independent sample t-test, with a sig. (2-tailed) 0.00 <0.05 then H1 is accepted, so it can be concluded that there is an influence of the STAD-type cooperative learning model on the understanding of the concepts of class IX students of SMP Negeri 25 Surabaya on static electricity.